Nutrition of Florida Citrus Trees, 3rd Edition: Chapter 11. Special Situations - Thomas A. Obreza; Brian J. Boman; Mongi Zekri; Stephen H. Futch; Lawrence R. Parsons; James J. Ferguson; Rhuanito Soranz Ferrarezi; Arnold Schumann (EDIS)
The information provided in the 2008 2nd edition is still sound for healthy citrus trees under Florida production conditions. Much of the information provided in this document on nutrients, application methods, leaf and soil sampling and irrigation scheduling are also effective for huanglongbing (HLB) affected citrus trees. However, research conducted since HLB was detected in Florida in 2005 has established changes in many production practices, including nutrient rates, irrigation scheduling, soil pH management, and use of Citrus Under Protective Screen (CUPS). Changes to the 2nd edition of SL253 will appear in boxes similar to this one at the beginnings of chapters 2, 6, 8, 9, and 11.